2022
DOI: 10.3390/cancers14122954
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Cancers: A Current Concise Overview of Breast and Prostate Cancer

Abstract: Cancer is a global issue, and it is expected to have a major impact on our continuing global health crisis. As populations age, we see an increased incidence in cancer rates, but considerable variation is observed in survival rates across different geographical regions and cancer types. Both breast and prostate cancer are leading causes of morbidity and mortality worldwide. Although cancer statistics indicate improvements in some areas of breast and prostate cancer prevention, diagnosis, and treatment, such st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 198 publications
0
23
0
Order By: Relevance
“…A recent Spanish study investigated occupational heat exposure and female breast cancer (Hinchliffe et al, 2021), which is shown to be related to prostate cancer (De Silva and Alcorn, 2022). The study observed positive associations for ever occupational heat exposure (OR 1.22; 95% CI 1.01, 1.46), and found those with higher lifetime cumulative exposures and durations were at even greater risk.…”
Section: Introductionmentioning
confidence: 97%
“…A recent Spanish study investigated occupational heat exposure and female breast cancer (Hinchliffe et al, 2021), which is shown to be related to prostate cancer (De Silva and Alcorn, 2022). The study observed positive associations for ever occupational heat exposure (OR 1.22; 95% CI 1.01, 1.46), and found those with higher lifetime cumulative exposures and durations were at even greater risk.…”
Section: Introductionmentioning
confidence: 97%
“…Despite the advances in understanding the etiology and the pathogenesis of PC, and the recognized high risk of men being diagnosed with the illness over their lifetime, an effective medication that can be safely delivered to favorably influence men's lives continues to be lacking 3 . There are different approaches to treat PC including radiotherapy, cryotherapy, hormone therapy, chemotherapy, immunotherapy, targeted therapy with surgery being the most common treatment for PC 4 , 5 . Although current treatments can improve the survival rate and the outcomes in men with metastatic prostate cancer, they all come with side effects such as erectile dysfunction and urinary incontinence which affects the patient’s quality of life 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…There are different approaches to treat PC including radiotherapy, cryotherapy, hormone therapy, chemotherapy, immunotherapy, targeted therapy with surgery being the most common treatment for PC 4 , 5 . Although current treatments can improve the survival rate and the outcomes in men with metastatic prostate cancer, they all come with side effects such as erectile dysfunction and urinary incontinence which affects the patient’s quality of life 4 , 5 . Additionally, the development of multidrug resistance towards current hormonal therapy and chemotherapeutic agents urges the need to discover novel compounds and targets for prostate cancer therapy 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular heterogeneity of BC can be attributed to genetic, epigenetic and non-genetic alterations in tumor epithelial cells and cells within the tumor microenvironment (TME) as well. Transformations can occur in multipotent mammary stem cells as well as in more differentiate cells [ 6 ], which can be followed by a malignant conversion switch, leading to metastasis to the lymph nodes or hematological metastasis to lung, brain and bone [ 7 ]. Distinct molecular profiles can impact the phenotype and the diverse biological behavior of breast cancer cells within primary tumors and metastasis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%